Theoretic and Methodological Supplying of Organizational Behavior - O. N. Gromova (Управление)
Investigations carried out at the Department of the theory of management, are the development of theoretical works previously performed by teachers of the Department. The grant received by the Department from the Ministry of education, facilitated the preparation and production of tutorial, workshop and collection of tables and diagrams on the subject “Organizational behavior”. In the development of this area was prepared and released an updated textbook on discipline “The theory of organization and organizational behavior”. All this caused the necessity of modernization of the theoretical-methodological support the development of competences, taught by the Department of educational basis, the contents of which is presented by this article.